Research Trend of Socio Scientific Issues (SSI) in Physics Learning Through Bibliometric Analysis in 2011-2020 using Scopus Database and the Contribution of Indonesia - Utama Alan Deta; Arika Arika; Dhila Linggar Lentika; Suliyanah Suliyanah; Setyo Admoko; Nadi Suprapto; Sayyidah Annimatus Sa’diyah Al Lathifah (Jurnal Penelitian Pendidikan IPA, 2021)
Socio-Scientific Issues (SSI) are controversial topics that have a scientific basis and important to society. This study aims to analyze the trends of SSI research publications from 2011-2020, visualize SSI research trends and how Indonesian researchers contribute to SSI research. This study was conducted on April 18, 2021, using bibliometric analysis. Data obtained is 225 data and taken by using Scopus database with "socio-scientific issues in physics" as the keyword from 2011 until 2020. After that, the data mapping was carried out using VOS Viewer software. Based on the result research, it can be concluded that the most topic in SSI research is related to scientific literacy, argumentation, and global warming. The visualization result shows that SSI has many effects on science learning, especially to improve argumentation skills. From 35 countries, Indonesia became the largest contribution research documents in SSI by placing two representative institutions: Universitas Pendidikan Indonesia and Universitas Negeri Yogyakarta. Indonesia also contributed the most prolific SSI writer, Widodo became the most prolific writer.